Microstrip Bandpass Filter With Reconfigurable Notch Response At 5.2 GHz Using Defected Microstrip Structure - Mutalib, M. A; Zakaria, Zahriladha; Shairi , Noor Azwan; Mohamad Isa, Mohd Sa'ari (Penerbit Universiti, UTeM, 2016)
-